2020
DOI: 10.1111/jora.12555
|View full text |Cite
|
Sign up to set email alerts
|

Parenting Practices, Family Obligation, and Adolescents’ Academic Adjustment: Cohort Differences with Social Change in China

Abstract: This study examined possible changes in the functions of parenting practices across different historical time points in terms of the effects of parenting practices on adolescents’ academic adjustment and their indirect effects via family obligation values. This study used a time‐lagged design that recruited Chinese high school students in 2010 (N = 1,040) and 2018 (N = 1,302). Structured equation modeling revealed the total effects of acceptance/involvement and strictness/supervision on academic adjustment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Cronbach’s α coefficient for this scale was 0.77. The Strictness/Supervision Scale has shown reasonable validity and reliability in Chinese adolescents in previous research (e.g., Liu, 2019 ; Bi et al, 2020 ).…”
Section: Methodsmentioning
confidence: 72%
“…Cronbach’s α coefficient for this scale was 0.77. The Strictness/Supervision Scale has shown reasonable validity and reliability in Chinese adolescents in previous research (e.g., Liu, 2019 ; Bi et al, 2020 ).…”
Section: Methodsmentioning
confidence: 72%
“…38,39 Previous research has indicated that broad cultural backgrounds may influence the effects of parentadolescent interactions on adolescents' developmental outcomes. 40,41 Therefore, the contemporary Chinese cultural context may provide a unique milieu to examine the relationships between family communication quality, autonomy, future orientation, and life satisfaction. We intended to investigate whether the relationships between these variables in the Chinese cultural context would be different from those in Western cultural contexts because of the influence of traditional Chinese culture or similar to those in Western cultural contexts because of the influence of individualism.…”
Section: The Chinese Cultural Contextmentioning
confidence: 99%
“…The interactions of parents and adolescents are embedded in a broad cultural background, and the effects of parenting practices are influenced by the match between parenting and cultural norms. 43 , 44 Since there are some unique characteristics of the Chinese cultural background, we would like to consider the effects of parenting practices in this specific cultural context. Unlike Western cultural values which place more importance on autonomy, traditional Chinese culture places particular emphasis on hierarchy and conformity to authority.…”
Section: Introductionmentioning
confidence: 99%